Representation of a dancing Shiva or Natesha - Temples of India Project Team (Jio Institute, 2024)
The representation of a dancing Shiva or Natesha is depicted in the niche on the cornice above the pillar of the mandapa (pillared hall) of the Bisaldeo Temple.